2006
DOI: 10.1517/14740338.5.3.469
|View full text |Cite
|
Sign up to set email alerts
|

Gefitinib: an adverse effects profile

Abstract: Gefitinib, an epidermal growth factor receptor inhibitor, is currently approved for use in patients with advanced non-small cell lung cancer who have failed previous chemotherapy or who are not suitable for chemotherapy in > 30 countries. The approved dose in patients with non-small cell lung cancer is 250 mg/day. The most common adverse effects are rash, diarrhoea, acne, dry skin, nausea and vomiting. Most of the effects are mild-to-moderate in nature and do not require discontinuation of therapy. The severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 59 publications
0
21
2
1
Order By: Relevance
“…Despite milder changes in cardiac contractility, wet lung weights were significantly increased with EKB-569 exposure. It is important to note that interstitial lung disease has been reported in a subset of patients receiving gefinitib in nonsmall cell lung cancer clinical trials (Cersosimo, 2006;Yoneda et al, 2006;Yamamoto et al, 2007). Although we did not observe increased pulmonary fibrosis, indirect evidence of pulmonary damage was supported by increased pulmonary proteinosis and thrombi with proteinaceous material in the RV of EGFR inhibitor treated mice.…”
Section: Discussioncontrasting
confidence: 43%
“…Despite milder changes in cardiac contractility, wet lung weights were significantly increased with EKB-569 exposure. It is important to note that interstitial lung disease has been reported in a subset of patients receiving gefinitib in nonsmall cell lung cancer clinical trials (Cersosimo, 2006;Yoneda et al, 2006;Yamamoto et al, 2007). Although we did not observe increased pulmonary fibrosis, indirect evidence of pulmonary damage was supported by increased pulmonary proteinosis and thrombi with proteinaceous material in the RV of EGFR inhibitor treated mice.…”
Section: Discussioncontrasting
confidence: 43%
“…Although the presence of somatic mutations in the EGFR gene is considered to be the best predictor of response to these TKIs (9,10,25,26), its efficacy as biomarker is not satisfactory due to technical problems on biopsy, secondary mutation acquiring the resistance to the EGFR TKIs, and recent data showing response of patients with wild-type EGFR to erlotinib (27). Thus, an alternative approach optimizing clinical outcome of EGFR TKI therapy is necessary to accurately select patients who will benefit from the therapy and to avoid critical adverse effects such as interstitial lung disease (28).…”
Section: Discussionmentioning
confidence: 99%
“…Onset of symptoms may begin only after 2 days of gefitinib therapy. Median onset was 24 days in Japan and 42 days in United States, and about 1 of 3 of the cases were fatal (28). It has been suggested that [ 18 F]FDG-PET may help to evaluate interstitial lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…The most common adverse effects of gefitinib treatment are rashes, diarrhea, acne, dry skin, nausea and vomiting. Although gefitinib-related interstitial lung disease is a well-known serious side effect that may result in death (11), most adverse effects of this drug are mild-to-moderate in nature and do not require the discontinuation of therapy (12). To date, adverse renal effects have been reported in only a few cases (2, 13, 14).…”
Section: Discussionmentioning
confidence: 99%